A facile and concise route to (hydroxybenzoyl)pyrido[2, 3-d]pyrimidine heterocycle derivatives: synthesis, and structural, spectral and computational exploration. Issue 59 (28th October 2019) - Ashraf, Abida; Khalid, Muhammad; Tahir, Muhammad Nawaz; Yaqub, Muhammad; Naseer, Muhammad Moazzam; Kamal, Ghulam Mustafa; Saifullah, Bullo; Braga, Ataualpa Albert Carmo; Shafiq, Zahid; Rauf, Waqar
Abstract : The chemical structures of the title compounds were ascertained by spectral techniques including 1 H, 13 C NMR, UV-vis and FT-IR spectroscopy as well as single-crystal X-ray diffraction, and DFT computation adopted to analyze the electronic structure. Abstract : In this work, we report the efficient synthesis of novel (hydroxybenzoyl)pyrido[2, 3- d ]pyrimidine heterocycle derivatives: 6-(2-hydroxy-5-methylbenzoyl)-1-methylpyrido[2, 3- d ]pyrimidine-2, 4(1 H, 3 H )-dione (6a ), 6-(5-fluoro-2-hydroxybenzoyl)-1-methylpyrido[2, 3- d ]pyrimidine-2, 4(1 H, 3 H )-dione (6b ), 6-(5-ethyl-2-hydroxybenzoyl)-1-methylpyrido[2, 3- d ]pyrimidine-2, 4(1 H, 3 H )-dione (6c ) and 6-(2-hydroxy-5-isopropylbenzoyl)-1-methylpyrido[2, 3- d ]pyrimidine-2, 4(1 H, 3 H )-dione (6d ). The chemical structures of the title compounds were ascertained by spectral techniques including 1 H, 13 C NMR, UV-visible and FT-IR spectroscopy as well as single-crystal X-ray diffraction analysis. Additionally, density functional theory (DFT) and time-dependent (TD-DFT) computation were adopted to analyze the electronic structures of 6a–d . Compounds 6a–d were computed in the ground state for FT-IR spectroscopic and natural bond orbital (NBO) analysis by DFT/B3LYP with the 6-311+G(d, p) basis set. UV-vis spectroscopic and HOMO and LUMO energy values for 6a–d were determined via TD-DFT/B3LYP with the 6-311+G(d, p) basis set. The optimized geometric parameters, UV-vis findings, and vibrational frequencies indicate good consistency with the experimental data. NBO analysis was conducted to explore the interactions and charge transfer among different orbitals in the title compounds. The HOMO and LUMO band gap (Δ E ) values for 6a–d were found to be 3.93, 3.91, 4.10 and 3.91 eV, respectively. Molecular electrostatic potential (MEP) analysis explored the reactivity of the title compounds by predicting their nucleophilic as well as electrophilic sites.